PENGARUH BAHAN AKTIF INSEKTISIDA CHLORPYRIFOS TERHADAP STRUKTUR HISTOLOGIS HEPAR IKAN WADER PARI (Rasbora lateristriata Bleeker, 1854) - Khoiruddin Anshori; Bambang Retnoaji (BERITA BIOLOGI, 2022)
The use of insecticides of the organophosphorus group is increasing along with the expansion of agricultural land. Chlorpyrifos (CPF) as one of the active ingredients can accumulate in the fish and impact human health through bioaccumulation and biomagnification mechanisms. This research aims to investigate the effects of sub-lethal exposure of CPF to yellow rasbora (Rasbora lateristriata) using mortality parameters and histological changes in the liver. One-month-old yellow rasbora larvae were exposed to CPF with concentrations of 0.001, 0.005, and 0.01 ppm for 168 hours based on the preliminary test. The paraffin method was used in the manufacture of liver histological preparations with Haematoxylin-Eosin staining. Observations were conducted descriptively-quantitatively to determine the type and extent of damage to the liver. The actual test results showed that the LC50 value of CPF against yellow wader for 168 hours was 0.078 ppm. The higher the concentration used shows a decrease in the survival rate of fish. Histological observations showed cell swelling, necrosis, and haemorrhagic tissue damage in CPF treatment. The increase in CPF concentration significantly affected cellular damage to hepatocyte cells, with the highest rate of damage at a concentration of 0.01 ppm.